Welcome To Tomorrow - Edward F. Rossomando (Wolters Kluwer Medknow Publications, 2010)
It is always a delight to see an idea become a reality. We recognized that there was a need for a dental journal for those to publish a tentative explanation for a phenomenon, an explanation that could be used as a basis for further investigation. Early in the planning, it was necessary to address the question: Is there a need for a journal for dental hypothesis? A detailed examination of dental journals now published revealed that most if not all published research findings - this research might be in various scientific disciplines or in education but all contained results of testing of a hypothesis. Some journals had sections for opinion but these too included the results of experiments. None allowed the publication of observations and an explanation of these observations - an hypothesis. But generating a hypothesis is an integral part of the scientific method, a process that begins with observation, proceeds to formulation of an explanation (the hypothesis), followed by experiments to test the hypothesis. Most disciplines have journals that publish the articles that include all three components - observation, hypothesis, and experimental results. Some disciplines have journals that publish theories; there is no requirement for the author to generate experimental results.